2020
DOI: 10.1038/s41565-019-0602-z
|View full text |Cite
|
Sign up to set email alerts
|

Waveguide-integrated van der Waals heterostructure photodetector at telecom wavelengths with high speed and high responsivity

Abstract: Intensive efforts have been devoted to exploit novel optoelectronic devices based on two-dimensional (2D) transition-metal dichalcogenides (TMDCs) owing to their strong lightmatter interaction and distinctive material properties [1,2]. In particular, photodetectors featuring both high-speed and high-responsivity performance are of great interest for a vast number of applications such as high-data-rate interconnects operated at standardized telecom wavelengths [3,4]. Yet, the intrinsically small carrier mobilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
232
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(249 citation statements)
references
References 57 publications
5
232
1
Order By: Relevance
“…The vdW integration could enable artificial heterostructures and superlattices with atomically-clean and electronicallysharp interfaces between highly disparate materials [191]. Recently, Nicolaus et al demonstrated a waveguide integrated MoTe 2 -graphene vdW heterostructure photodetector [192], for which the responsivity is about 0.2 A/W at 1300 nm and the normalized photo-dark-current (NPDR) ratio is almost an order of magnitude than pure-graphene photodetectors due to the bandgap in MoTe 2 . Moreover, the vertical MoTe 2 -graphene heterostructure design minimizes the carrier transit path length in TMDs and enables a record measured bandwidth of >24 GHz.…”
Section: Discussionmentioning
confidence: 99%
“…The vdW integration could enable artificial heterostructures and superlattices with atomically-clean and electronicallysharp interfaces between highly disparate materials [191]. Recently, Nicolaus et al demonstrated a waveguide integrated MoTe 2 -graphene vdW heterostructure photodetector [192], for which the responsivity is about 0.2 A/W at 1300 nm and the normalized photo-dark-current (NPDR) ratio is almost an order of magnitude than pure-graphene photodetectors due to the bandgap in MoTe 2 . Moreover, the vertical MoTe 2 -graphene heterostructure design minimizes the carrier transit path length in TMDs and enables a record measured bandwidth of >24 GHz.…”
Section: Discussionmentioning
confidence: 99%
“…Black phosphorus could be another promising material in terms of photodetection owing to its direct and tunable bandgap, as well as the high sensitivity in the near-and mid-infrared regimes [224][225][226]. Black phosphorus analogs, such as Bi, Te, and SnS, have also been [233] Exfoliated graphene and hBN Si strip waveguide 0.36 42 Schuler et al [234] Exfoliated graphene Si slot waveguide 0.076 65 Flöry et al [235] vdWs heterostructure Si strip waveguide 0.2 27 Goykhman et al [236] CVD graphene Si-Au Schottky structure 0.37 Not mentioned Ding et al [35] CVD graphene Plasmonic slot waveguide 0.36 >110 Ma et al [221] CVD graphene Si 3 N 4 strip waveguide with metallic bowtie structures 0.5 >110 Guo et al [237] CVD graphene Si-plasmonic hybrid waveguide 0.4 >40 Chen et al [222] Exfoliated BP Si-plasmonic 3D integration 10 0.150 applied in the photodetection, but with moderate responsivity and response speed [196,227,228]. Multiple works of the BP photodetector based on both free-space and waveguide-integrated schemes were reported.…”
Section: Hybrid 2d Materials Plasmonic Photodetectorsmentioning
confidence: 99%
“…The large‐scale semiconducting 2H‐MoTe 2 with single‐crystalline domain size up to hundreds of micrometer has been synthesized by the unique phase transition between 1T'‐ to 2H‐MoTe 2 . [ 13 ] Due to the moderate bandgap of few‐layer 2H‐MoTe 2 of 1.0 eV, ambipolar charge transport [ 14 ] and optical devices operated at standardized telecom wavelengths [ 15 ] have been reported using MoTe 2 . Monolithic integration allows both the electronics and the optical devices to be integrated with van der Waals MoTe 2 in a single growth process.…”
Section: Figurementioning
confidence: 99%